PERBEDAAN STRATEGI KESANTUAN DALAM PERCAKAPAN UNTUK PEMBELAJAR BAHASAJEPANG TINGKAT SHOKYUU DAN TINGKAT CHUUKYUU - Reny Wiyatasari; Maharani P.Ratna (Universitas Diponegoro, 2014)
AbstractThe purpose of this paper is to know the politeness strategy dan expressions which are exist in expressions contain of politeness strategy in Japanese conversation class for basic level and intermediate level. The data sources are the conversation part of book titled Minna No Nihongo Shokyuu 2 dan Minna No Nihongo Chuukyuu 1. Based on the analysis result, there are 110 datas found in basic level, and 68 datas are found in intermediate level. As a result, positive politeness strategy (sub strategy 2) is the most found politeness strategy in basic level, while negative politeness strategy (sub strategy 1) is the most found politeness strategy in intermediate level. The type of expressions that are found in expressions contain of positive politeness strategy (sub strategy 2), such as ～ndesuka（ んですか）, desuka (～ですか), while the type of expressions that are found in expressions contain of negative politeness strategy (sub strategy 1), such as Chotto te mo ii desuka (ちょっと～てもいいですか), Chotto te itadakenaideshouka (ちょっと～ていただけないでしょうか).